New approaches to the treatment and prevention of cardiovascular diseases and microcirculatory disorders in patients with anxiety and autonomic disorders - E. N. Dyakonova; V. V. Makerova; N. V. Vorob’eva (Лечащий Врач, 2021)
Cardiovascular disease (CVD) is one of the most common causes of morbidity and mortality in the world. Data on the prevalence of anxiety and depression among patients with CVD are presented. The main risk factors and pathophysiological mechanisms supporting the formation of comorbid disorders are considered. The relationship between anxiety-depressive states, disorders of autonomic regulation, endocrine disorders, inflammation and pathology of the circulatory system is demonstrated. The results of studies on the problems of diagnosis and treatment of CVD complicated by affective or neurotic disorder are described. Particular attention is focused on the questions of drugs safety and increasing patient compliance. Using domestic studies as an example, the efficacy and safety of using a drug containing affinitypurified technologically processed antibodies in high dilutions to the brain-specific protein S100 in the correction of psychoemotional disorders in patients with CVD pathology were demonstrated. The results of an open clinical study of the use of the drug in young patients with grade I arterial hypertension are presented.